Chronic obstructive pulmonary disease: in-depth analysis of microbiota association and innovative prevention and treatment approaches from the gut-lung axis perspective - Wang, Yubo; Li, Xinyu; Gao, Feng (Frontiers in Immunology, 2025)
The pathogenesis of chronic obstructive pulmonary disease (COPD) is complex and affects multiple systems. This article focuses on COPD and elaborates on the roles of the lung and gut microbiota as well as preventive and therapeutic strategies. Innovatively, this article reveals the impact of the connection between the lung and gut microbiota via the gut-lung axis on COPD, clarifies the association between changes in the lung microbiota and clinical features, enriches the understanding of the correlation between gut dysbiosis and COPD, breaks through the limitations of single-organ research, and opens up a completely new path for uncovering the underlying pathogenesis of COPD. In terms of prevention and treatment, gut microbiota-targeted therapies (fecal microbiota transplantation, probiotics and prebiotics) provide new ideas and evidence. Research on dietary factors (vitamins, dietary fiber) helps with precise nutritional interventions and highlights the significance of dietary adjustments. The multi-target actions of natural compounds integrate traditional and modern medicine and lay the foundation for the development of new approaches, which is of great significance and value for COPD research, clinical translation, and the improvement of patient health.